2008 2nd International Conference on Bioinformatics and Biomedical Engineering 2008
DOI: 10.1109/icbbe.2008.298
|View full text |Cite
|
Sign up to set email alerts
|

The Acute and Chronic Toxicity of Five Heavy Metals on the Daphnia Magna

Abstract: The acute and chronic toxicity experiments were conducted towards D. magna for five heavy metals, namely Hg, Cd, Cu, Pb and Cr, existing in single or mixture. The single results suggested that Hg was the most toxic, and then Cd, Cu, Pb and Cr in turn. The joint experiments indicated that toxicity for all mixtures were synergistic to D. magna using Toxic Units (TU s ) and Additional Index (AI). For more toxic Hg-Cd-Cu-Pb-Cr mixture and Hg-Cd mixture, toxicity enhancement index (TEI), a measurement index of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…The results of this study are not in agreement with those obtained by Meng et al, [18] that investigated the toxicity of Hg-Cd-Cu, Hg-Cd, and Cu-Cd mixtures on D. magna. The mixture experiments indicated that toxicity for all mixtures was synergistic.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…The results of this study are not in agreement with those obtained by Meng et al, [18] that investigated the toxicity of Hg-Cd-Cu, Hg-Cd, and Cu-Cd mixtures on D. magna. The mixture experiments indicated that toxicity for all mixtures was synergistic.…”
Section: Resultscontrasting
confidence: 72%
“…[16][17][18] The copepod T. fulvus is an euryaline harpacticoid of high ecological importance, living in rocky coastal Mediterranean microenvironments. It has already been used for toxicity testing, [19][20][21] and represents a standardised species, for ecotoxicological studies, for the Italian legislation.…”
Section: Introductionmentioning
confidence: 99%